2010
DOI: 10.1016/j.vaccine.2010.08.036
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of long-term humoral memory development after immunisation against Neisseria meningitidis B or diphtheria toxoid

Abstract: Since genome sequence data became available there has been a marked increase in number of protein antigens that have been suggested as prospective vaccine components against Neisseria meningitidis B (MenB). Few studies have addressed the mechanisms by which meningococcal vaccines generate and sustain immunological memory. The goal of this study was to compare the B-cell response (antibody-secreting cells [ASC], memory B cell and IgG) evoked by a MenB vaccine (VA-MENGOC-BC(®)) with the B-cell response to diphth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
1

Year Published

2011
2011
2016
2016

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 20 publications
0
4
1
Order By: Relevance
“…In contrast to previously published ELISA data 12, using the in vitro neutralization test we did not detect diphtheria antibodies before or after one injection of vaccine. However, as shown in Figure 3A, all animals had protective neutralizing antibody titers (≥0.1 IU/mL) after two doses of vaccine (mean of 1.84 IU/mL) with a significant (P = 0.005) increase of antibodies after the third injection of DTP vaccine (mean of 21.2 IU/mL).…”
Section: Kinetics Of Dt Neutralizing Antibody Response To the Dtp Vaccontrasting
confidence: 99%
See 2 more Smart Citations
“…In contrast to previously published ELISA data 12, using the in vitro neutralization test we did not detect diphtheria antibodies before or after one injection of vaccine. However, as shown in Figure 3A, all animals had protective neutralizing antibody titers (≥0.1 IU/mL) after two doses of vaccine (mean of 1.84 IU/mL) with a significant (P = 0.005) increase of antibodies after the third injection of DTP vaccine (mean of 21.2 IU/mL).…”
Section: Kinetics Of Dt Neutralizing Antibody Response To the Dtp Vaccontrasting
confidence: 99%
“…After 6 months of primary immunization, about 70% of the animals still had protective neutralizing DT antibodies, but none had significant bactericidal antibodies to MenB. A long-lasting antibody-secreting cell response was also seen for the DTP vaccine compared to the Cuban MenB vaccine 12.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…This is followed by an antigen‐specific ELISPOT assay for the detection of memory B cells that have differentiated into antibody‐secreting cells (ASCs) in vitro . Memory B cell ELISPOT assay has been used previously to quantify the number of memory B cells present in peripheral blood in relation to different vaccines [28–32]. In this study, we have adapted this memory B cell ELISPOT assay to examine the Ro/SSA‐ and La/SSB‐ specific memory B cell pattern in the peripheral blood of patients with pSS.…”
Section: Introductionmentioning
confidence: 99%
“…The Cuban MenB vaccine (VA-MENGOC-BC H ) employed in this study was previously used in Brazil to immunize millions of children but showed unsatisfactory efficacy (3). Since then, we have been studying the ability of this vaccine to generate and maintain immunological memory (6,7,12).…”
Section: Discussionmentioning
confidence: 99%